The Fourth Graders' Critical Thinking Skills on Social Study Lesson - Fajrianti, Fajrianti; Hartono, Hartono; Nugroho, Sunyoto Eko (Educational Management, 2021)
Current learning directs 21st-century learning skills such as communication, collaboration, critical thinking, and problem-solving skills. These skills are the targets of 2013 curriculum learning with HOTS question forms, which allow them to think, analyze, and utilize critical thinking skills. Therefore, critical thinking skills as assessment processes or decision-making should consider the facts, situation, concepts, methods, and criteria in the learning process. This research aims to analyze fourth-graders' critical thinking skills in social study lessons. This research is qualitative. The data were collected through interviews, observation, and documentation. The data validity was done by source triangulation. The data analysis was done simultaneously with data collection. It consisted of data reduction, display, and conclusion. The findings showed that the fourth graders' critical thinking skills of Public Primary School 64 Buton consisted of 3 categories. They were (1) high critical thinking skills students with a percentage score of 23.3%, (2) moderate critical thinking skill students with a percentage of 54%, and (4) low critical thinking skill students with 23.3%.